2016
DOI: 10.1155/2016/6172453
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Adaptive Window Size Selection Method for Improving Spectrogram Visualization

Abstract: Short Time Fourier Transform (STFT) is an important technique for the time-frequency analysis of a time varying signal. The basic approach behind it involves the application of a Fast Fourier Transform (FFT) to a signal multiplied with an appropriate window function with fixed resolution. The selection of an appropriate window size is difficult when no background information about the input signal is known. In this paper, a novel empirical model is proposed that adaptively adjusts the window size for a narrow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…In the first step, it is manifested that the frequency band, wherever the acoustic signal has strong components, correlated to relative interfering comprised noise and signals. Consequently, STFT is tuned (window size) [40][41][42][43][44] to non-stationary underwater signals and revealed that the presence of leakage acoustic signal is analogously strong in short-time windows related to other unwanted events (see Figure 4). However, due to an enormous number of mother wavelets availability with different localization properties and scales, it provokes to tune the WT to underwater acoustic signals regarding the nature of events.…”
Section: General Methods Of Underwater Leakage Identificationmentioning
confidence: 99%
“…In the first step, it is manifested that the frequency band, wherever the acoustic signal has strong components, correlated to relative interfering comprised noise and signals. Consequently, STFT is tuned (window size) [40][41][42][43][44] to non-stationary underwater signals and revealed that the presence of leakage acoustic signal is analogously strong in short-time windows related to other unwanted events (see Figure 4). However, due to an enormous number of mother wavelets availability with different localization properties and scales, it provokes to tune the WT to underwater acoustic signals regarding the nature of events.…”
Section: General Methods Of Underwater Leakage Identificationmentioning
confidence: 99%
“…The first step in identifying the location of a cyst and eliminating the clutter inside it starts with calculating the energy of the envelope signal for each of the image lines using the windowing technique [6]. Mapping the envelope signal into energy through the windowing process helps to classify and differentiate from the speckle destructive region and the clutter inside the cyst.…”
Section: Methodsmentioning
confidence: 99%
“…It must be noticed that there is a strict relationship between the representations resolutions in time and frequency domains. If the time period Δ T is increasing, the frequency resolution Δ F is simultaneously decreasing [49,50]. The best resolution is maintained when Δ F = 1/Δ T .…”
Section: Time-frequency Domain Analysis Of Mbnmentioning
confidence: 99%